解方程 ①x2+2x-99=0 ②(2x-1)2=x(6x-3) ③4x2-8x+1=0 ④(2x-3)2-121=0 ⑤x2-2
⑥2(x-3)2=9-x2 ⑦-3x2-4x+4=0 ⑧(x+1)(x-1)+2(x+3)=8 ⑨(x+1)2=4(x-2)2. |
①x2+2x-99=0,
(x+11)(x-9)=0,
x+11=0,x-9=0,
x1=-11,x2=9.
②(2x-1)2=x(6x-3),
(2x-1)2-3x(2x-1)=0,
(2x-1)(2x-1-3x)=0,
2x-1=0,2x-1-3x=0,
x1=
,x2=-1.1 2
③4x2-8x+1=0,
b2-4ac=(-8)2-4×4×1=48,
x=
,8± 48 2×4
x1=
,x2=2+ 3 2
.2- 3 2
④(2x-3)2-121=0,
(2x-3+11)(2x-3-11)=0,
2x-3+11=0,2x-3-11=0,
x1=-4,x2=7.
⑤x2-2
x+3=0,3
(x-
)2=0,3
x-
=0,3
x1=x2=
.3
⑥2(x-3)2=9-x2,
2(x-3)2-(x+3)(x-3)=0,
(x-3)(2x-6-x-3)=0,
x-3=0,x-9=0,
⑦-3x2-4x+4=0,
3x2+4x-4=0,
(3x-2)(x+2)=0,
3x-2=0,x+2=0,
x1=
,x2=-2.2 3
⑧(x+1)(x-1)+2(x+3)=8,
整理得:x2-2x-3=0,
(x-3)(x+1)=0,
x-3=0,x+1=0,
x1=3,x2=-1.
⑨(x+1)2=4(x-2)2.
x+1=±2(x-2)
x1=-5,x2=1.